Formulasi Hand Sanitizer Gel dengan Ekstrak Buah Terung Belanda (Solanum Betaceum Cav) Sebagai Antiseptik - Vivi Ramadhani Tanjung; Dewi Rahmawati; Alhara Yuwanda (Publikasi Indonesia, 2023)
Dutch eggplant fruit (Solanum Betaceum Cav) has chemical contents including alkaloids, flavonoids, tannins, saponins and triterpenoids which are known to have antibacterial activities (Rahmadina and Sudiono 2019). Based on the compounds that are owned Dutch eggplant fruit can be used as a hand antiseptic. This study aims to formulate Dutch eggplant fruit extract (Solanum betaceum Cav) in the form of hand sanitizer preparations. Gel Hand sanitizer extract Dutch eggplant fruit is formulated with different concentrations. The method used is the Disc Diffusion Method (Kirby Bauer Method). Gel Hand sanitizer is tested for its physical properties, including Organoleptis test, homogeneity test, PH test, stability test, irritation test and antibacterial test. Hand sanitizer gel preparations that have antibacterial activity against staphylococcus aureus bacteria are at a concentration of 15%, which is 4.51 mm.